2017
DOI: 10.1097/mib.0000000000001235
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Gene Panel Sequencing for Early-onset Inflammatory Bowel Disease and Chronic Diarrhea

Abstract: Targeted gene panel sequencing is a fast and effective screening method for monogenic causes of eoIBD that should be routinely established in national referral centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Nonetheless, one needs to analyse separately patients who benefited from TNGS as a first screening test [13 molecular diagnoses out of 49 patients, 26.5%] and patients who were functionally tested [eight molecular diagnoses out of 77 patients, 10%]. Altogether our findings confirm and extend results obtained in two previous studies in smaller cohorts of VEO-IBD patients, in which TNGS could identify causative mutations in 4/25 1 and in 5/71 patients, 14 respectively. Furthermore, in patients with higher genetic heterogeneity such as those with isolated colitis, TNGS is more efficient [68% of monogenic defects were identified by TNGS in this group] as it can reveal diagnosis in patients with atypical clinical presentation, as exemplified in the present study in one girl with XIAP deficiency.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Nonetheless, one needs to analyse separately patients who benefited from TNGS as a first screening test [13 molecular diagnoses out of 49 patients, 26.5%] and patients who were functionally tested [eight molecular diagnoses out of 77 patients, 10%]. Altogether our findings confirm and extend results obtained in two previous studies in smaller cohorts of VEO-IBD patients, in which TNGS could identify causative mutations in 4/25 1 and in 5/71 patients, 14 respectively. Furthermore, in patients with higher genetic heterogeneity such as those with isolated colitis, TNGS is more efficient [68% of monogenic defects were identified by TNGS in this group] as it can reveal diagnosis in patients with atypical clinical presentation, as exemplified in the present study in one girl with XIAP deficiency.…”
Section: Discussionsupporting
confidence: 86%
“… 9 , 12 , 13 More recently, TNGS could identify causative mutations in small cohorts of VEO-IBD patients. 1 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the huge amount of retrieved data and the risk of incidental findings in other non-PID genes involved in different monogenic or multifactorial pathologies may be confounding and do not corresponding to the first suspicion. Additionally, the confidence of the results decreases with the number of targeted genes and may preclude any variant detection in self-evident known genes (65). Many previously undetected variants do not have a well-defined role in our genome (1.5 × 10 6 million variants in each genome and lesser in exome).…”
Section: Discussionmentioning
confidence: 99%
“…4,13 Petersen et al reported that targeted gene panel sequencing revealed monogenic disease in 5 of 71 patients with earlyonset inflammatory bowel disease and chronic diarrhea. 14 In another large cohort of inflammatory bowel disease patients presenting before 2 years of age, 31% of 62 patients had monogenic diseases. 15 In our study, the diagnostic rates were 71.9% (46/64) for targeted gene panel sequencing and 57.5% (42/73) for exome sequencing (p = 0.081).…”
Section: Discussionmentioning
confidence: 99%